Sejarah nusantara : the Malay Archipelago / Alfred Russel Wallace ; penerjemah, Ahmad Asnawi, H. Supriyanto Abdullah, Sutrisno ; penyunting, Ayuninda Erdiani - WALLACE, Alfred Russel; Ahmad Asnawi; Supriyanto Abdullah , H.; Sutrisno; Ayuninda Erdiani (Indoliterasi, 2015)
iv, 856 hlm. : ilus. ; 23 cm.